Annual Harvest Festival for local producers and vendors of organic foods at Dewick-MacPhie Dining Hall. Photo 020 - Tobin, Joanie (Tufts Archival Research Center, 2008)
Annual Harvest Festival for local producers and vendors of organic foods at Dewick-MacPhie Dining Hall.